2020
DOI: 10.3390/life10110270
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Effects of Hypolipidemic Treatment in Children with Familial Hypercholesterolemia in Poland

Abstract: Familial hypercholesterolemia (FH) is the most common monogenic autosomal dominant disorder. FH results in an increased cardiovascular mortality rate. However, cardiovascular risk control factors enable the avoidance of approximately 80% of strokes and cardiovascular diseases. Therefore, early detection and implementation of lipid-lowering treatment is essential. In the present study, 57 pediatric patients aged 9.57 ± 3.26 years with FH were enrolled in the study. Researchers checked the lipid profile and perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Delay of the treatment can cause future CVD development. There is growing scientific evidence that statin therapy in pediatric patients is safe and effective [ 7 , 26 , 27 ]. Statin therapy may be initiated in children ≥ 10 years of age (except for children with FH, in whom the Forum of Lipid Experts in Poland recommends the use of statins > 8 years of age (accumulating data support lowering of this age even to 6 years), and in children with homozygous FH < 8 years of age with LDL-C concentration > 500 mg/dl (12.9 mmol/l)) [ 10 ].…”
mentioning
confidence: 99%
“…Delay of the treatment can cause future CVD development. There is growing scientific evidence that statin therapy in pediatric patients is safe and effective [ 7 , 26 , 27 ]. Statin therapy may be initiated in children ≥ 10 years of age (except for children with FH, in whom the Forum of Lipid Experts in Poland recommends the use of statins > 8 years of age (accumulating data support lowering of this age even to 6 years), and in children with homozygous FH < 8 years of age with LDL-C concentration > 500 mg/dl (12.9 mmol/l)) [ 10 ].…”
mentioning
confidence: 99%
“…However, when data from Greece, where population-based screening was conducted between the 1st and 3rd years of age, were excluded from the analysis, the mean reduction in LDL-C during statin treatment was much greater, i.e., 33.5% [18]. Another study from Poland showed a 34.4% decrease in LDL-C following one-year treatment with rosuvastatin, although at different doses [19].…”
Section: Discussionmentioning
confidence: 99%
“…lipid profile). Early lifestyle and pharmacologic intervention improve outcomes even in the paediatric population [5].…”
mentioning
confidence: 99%